Внутренний маркетинг как фактор профессионального развития педагогического персонала школы - Донина, Ирина Александровна (International Dialogues on Education Journal, 2017)
This article is devoted to the consideration of new approaches to the professional development factor of school teaching staff as a heterogeneous organization. In many ways, the success of professional teachers development in modern social and economic conditions depends on the school philosophy, its organizational culture, as well as the characteristics of the control system architecture: flexibility, adaptability, administration and teaching staff availability for the introduction in the administrative activity practice of innovative approaches in the management and marketing fields. The article shows that internal marketing is classified as factors ensuring sustainable competitive school advantage and can form the basis for the effective search ways of interaction between teachers, students, support staff, the social partners, employers, given the concept of internal marketing, defined its goals and objectives , its role disclosed in the professional development of school personnel management system.